POWER AND INFORMATION SYSTEM OF LINEAR COMPLEX OF SWITCHING DEVICES - Andrey Koltsov; Gennady Kovtun; Yurii Goryushin; Irina Ivanitskaya; Nikolai Yazichenkov; Andrei Voloshin; Oleg Savotin; Dmitrii Lebedev (Вестник Северо-Кавказского федерального университета, 2022)
Power lines icing can cause serious accidents up to fall of poles and wire break. An effective way , get rid of ice on wires is its fusion of electric shock. For the melting of ice is necessary to create a path that is currently outside the substations is performed using the organization of short-circuit distribution point, or by the organization of temporary short-circuiting between the wires. First method requires significant financial and time investments; another one is not fully reliable and safe. Using of linear complex of switching devices mounted on power line poles, helps to remove these shortcomings. The complex has its own power and self-diagnostic systems. This article discusses issues of the organization and operation of power system of the linear complex of switching devices that are installed on 220 kV and 330 kV AC OHTL and presents features of the information system of the linear complex of switching devices such as online remote status control.